2019
DOI: 10.1021/acs.energyfuels.9b01212
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Antifouling Mechanism of Electroless Nickel–Phosphorus Coating against Sand and Bitumen

Abstract: Antifouling coatings have attracted much attention in applications of industrial equipment and systems. The accumulation of foulants on downhole equipment used in the steam-assisted gravity drainage process for oil sand extraction reduces the recovery efficiency of bitumen and causes failures of the equipment. Applying suitable coatings is expected to endow antifouling property to the related substrate surface. Understanding the interaction mechanism between foulants and antifouling coating is critical for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Furthermore, it was observed that the intensity of the XRD peaks decreases as the surface roughness of the substrate decreases. This suggests that the coating is more evenly deposited on a rougher substrate surface compared to a smoother one This suggests that the crystalline structure of the coating is influenced by the roughness of the substrate [15]. The XRD analysis also revealed an overlap between the peaks corresponding to graphene and nickel in the coating.…”
Section: Crystallite Structure Of Deposited Coatingsmentioning
confidence: 92%
“…Furthermore, it was observed that the intensity of the XRD peaks decreases as the surface roughness of the substrate decreases. This suggests that the coating is more evenly deposited on a rougher substrate surface compared to a smoother one This suggests that the crystalline structure of the coating is influenced by the roughness of the substrate [15]. The XRD analysis also revealed an overlap between the peaks corresponding to graphene and nickel in the coating.…”
Section: Crystallite Structure Of Deposited Coatingsmentioning
confidence: 92%
“…The Derjaguin–Landau–Verwey–Overbeek (DLVO) model for colloidal forces ( F dlvo ), which includes van der Waals forces ( F vdw ) and electrical double-layer forces ( F edl ), was used to describe the surface forces acting between the Se 0 probe and Fe­(OH) 3 surface. A constant charge DLVO model was applied for the theoretical calculation in the case of a sphere approaching to an infinite flat substrate. ,,, The equations are described as follows where A is the Hamaker constant for the Se 0 probe interacting with Fe­(OH) 3 across water, R is the Se 0 probe radius, D is the separation distance between the Se 0 probe and flat Fe­(OH) 3 surface, ε is the relative permittivity, ε 0 is the vacuum permittivity, σ T is the probe surface charge density, σ S is the substrate surface charge density, κ is the Debye length, k B is the Boltzmann constant, T is the temperature, C 0 is the bulk concentration of ions, N A is Avogadro’s number, and e is the elementary charge. The surface potential Ψ is correlated to the surface charge density by the Grahame equation (eq ).…”
Section: Methodsmentioning
confidence: 99%
“…A constant charge DLVO model was applied for the theoretical calculation in the case of a sphere approaching to an infinite flat substrate. 35,36,44,45 The equations are described as follows…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation